2018
DOI: 10.2460/javma.253.5.579
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the effects of gabapentin on activity levels and owner-perceived mobility impairment and quality of life in osteoarthritic geriatric cats

Abstract: OBJECTIVE Toevaluate effects of gabapentin on activity levels and owner-perceived mobility impairment and quality of life (QOL) in osteoarthritic geriatric cats. DESIGN Blinded, placebo-controlled, randomized crossover-design study. ANIMALS 20 osteoarthritic cats (≥ 10 years old). PROCEDURES Cats received gabapentin (10 mg/kg [4.5 mg/lb]) or placebo treatment, PO, every 12 hours for 2 weeks, followed by the alternate treatment (with no washout period). Activity was assessed with a collar-mounted accelerometer.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(56 citation statements)
references
References 32 publications
2
53
1
Order By: Relevance
“…Gabapentin's main side effects in cats are sedation and ataxia (anecdotal mentioning of diarrhoea, vomiting and hyper-salivation) with a dose ranging from 10 to 30.5 mg/kg. 39,42,43 No side effects were registered during observations with the study's lower dose of 5 mg/kg; however, activity and heart rate were not measured and a mild level of sedation cannot be ruled out.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Gabapentin's main side effects in cats are sedation and ataxia (anecdotal mentioning of diarrhoea, vomiting and hyper-salivation) with a dose ranging from 10 to 30.5 mg/kg. 39,42,43 No side effects were registered during observations with the study's lower dose of 5 mg/kg; however, activity and heart rate were not measured and a mild level of sedation cannot be ruled out.…”
Section: Discussionmentioning
confidence: 95%
“…35,36 In veterinary medicine, gabapentin finds an application in dogs' refractory idiopathic epilepsy and it is also the most prescribed treatment for the alleviation of chronic musculoskeletal pain in cats. [37][38][39] Actions leading to pain management have been ascribed to its binding to alpha 2 delta-1 subunits of voltagegated calcium channels in the brain, inhibiting membrane and anterograde trafficking. 40 In the present study pain was assessed at 6 h after extubation via the Colorado State University Feline Acute Pain Scale, which was recently validated for interoperator reliability for ovariohysterectomy in cats.…”
Section: Discussionmentioning
confidence: 99%
“…40 A 14-day trial using gabapentin at 10 mg/kg q12h showed an improvement as determined by a CSOM CMI, but a decrease in activity levels was noted, with sedation being the most common side effect. 46 < Opioids While it has been reported that opioids are commonly prescribed for chronic musculoskeletal pain in cats by North American veterinarians, 66 they are often only prescribed for short periods (8-10 days), which likely reflects the lack of a licensed opioid that can be easily administered at home. In addition, in the UK some opioids are a class B drug, restricting their availability and use.…”
Section: Cats With Chronic Musculoskeletal Pain Have Demonstrated Sigmentioning
confidence: 99%
“…45 This CSOM tool was also used in a randomised, placebo-controlled, crossover study assessing gabapentin, which found a significant treatment effect using the CMI. 46 The value of a CSOM-based CMI over a CMI that is not based on the individual has therefore yet to be determined.…”
Section: Diagnosis Of Feline Musculoskeletal Impairmentmentioning
confidence: 99%
“…Adjunctive drug therapy has been introduced to feline pain management regimens, but research is limited with variable results. In a recent study on gabapentin for the treatment of feline osteoarthritis, there was owner-assessed improvement in impaired activities, but overall activity counts were lower and sedation was commonly reported (27). Tramadol improved the activity levels of arthritic cats in one study (28), but in another had no added benefit when combined with meloxicam vs. meloxicam alone (29).…”
Section: Introductionmentioning
confidence: 98%